Synthesis of triphenylene-fused phosphole oxides via C-H functionalizations - Md. Shafiqur Rahman (2021)
The synthesis of triphenylene-fused phosphole oxides has been achieved through two distinct C-H functionalization reactions as key steps. The phosphole ring was constructed by a three-component coupling of 3-(methoxymethoxy)phenylzinc chloride, an alkyne, and dichlorophenylphosphine, involving the regioselective C-H activation of the C2 position of the arylzinc intermediate via 1,4-cobalt migration. The resulting 7-hydroxybenzo[b]phosphole derivative was used for further π-extension through Suzuki-Miyaura couplings and a Scholl reaction, the latter closing the triphenylene ring. The absorption and emission spectra of the thus-synthesized compounds illustrated their nature as hybrids of triphenylene and benzo[b]phosphole.